Drought × disease interaction in Eucalyptus globulus under Neofusicoccum eucalyptorum infection. (5th April 2017) - Barradas, C.; Pinto, G.; Correia, B.; Castro, B.B.; Phillips, A. J. L.; Alves, A.
Abstract : Eucalyptus species are widely spread over the world, being extensively planted and exploited by industries. Drought and pathogens are known to affect the establishment and productivity of Eucalyptus plantations worldwide. The aim of this work was to evaluate the pathogenicity of Neofusicoccum eucalyptorum in drought‐stressed and well‐watered E. globulus plants. The effect of a previous drought priming step and the role of water status at the time of inoculation were evaluated. Lesion length, plant growth and physiological parameters (relative water content, water potential, photosynthetic pigments and lipid peroxidation) were determined. The results indicate that water‐stressed plants were more susceptible to N. eucalyptorum than non‐stressed ones. However, this response was particularly relevant when the plants were inoculated while water limitation was already occurring. Moreover, drought‐primed plants were slightly more resistant to fungal infection than the non‐primed ones. This study reinforces the importance of exploring drought × disease interaction in Eucalyptus and the underlying physiological responses involved in plant performance.